2015
DOI: 10.1089/ars.2013.5803
|View full text |Cite
|
Sign up to set email alerts
|

The Protein Oxidation Repair Enzyme Methionine Sulfoxide Reductase A Modulates Aβ Aggregation and ToxicityIn Vivo

Abstract: Aims: To examine the role of the enzyme methionine sulfoxide reductase A-1 (MSRA-1) in amyloid-b peptide (Ab)-peptide aggregation and toxicity in vivo, using a Caenorhabditis elegans model of the human amyloidogenic disease inclusion body myositis. Results: MSRA-1 specifically reduces oxidized methionines in proteins. Therefore, a deletion of the msra-1 gene was introduced into transgenic C. elegans worms that express the Ab-peptide in muscle cells to prevent the reduction of oxidized methionines in proteins. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 76 publications
0
13
0
Order By: Relevance
“…However, Met35 can play a role in AD pathogenesis due to putative interactions in the biological systems. It has been shown that in a Caenorhabditis elegans model of inclusion body myositis the knockout of MSRA-1 reduces the aggregation of Aβ into insoluble aggregates [33] , however in this case the aggregation is intracellular. Even small differences in the peptide aggregation properties may be crucial in triggering the molecular events leading to the disease, however the lower amyloidogenity and the unaffected ability to catalyze redox reactions when bound to copper ions suggest that Met35 oxidation is most likely not essential in AD.…”
Section: Discussionmentioning
confidence: 99%
“…However, Met35 can play a role in AD pathogenesis due to putative interactions in the biological systems. It has been shown that in a Caenorhabditis elegans model of inclusion body myositis the knockout of MSRA-1 reduces the aggregation of Aβ into insoluble aggregates [33] , however in this case the aggregation is intracellular. Even small differences in the peptide aggregation properties may be crucial in triggering the molecular events leading to the disease, however the lower amyloidogenity and the unaffected ability to catalyze redox reactions when bound to copper ions suggest that Met35 oxidation is most likely not essential in AD.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the expression of antioxidant proteins via the Nrf2-antioxidant response element (ARE)-signaling pathway is upregulated when MsrA is missing [15] , [16] , [17] . Moreover, low activity of MsrA has been associated with formation of protein aggregates in Parkinson's and Alzheimer's disease as well as inclusion body myositis [18] , [19] , [20] , [21] , but the implications of these protein aggregates on repair and cell death pathways in MsrA deletion models has remained unstudied. In models of neurodegenerative diseases and proteinopathies of the liver, misfolded or unrepaired defective proteins colocalize with p62, also called sequestosome 1 (SQSTM1), a ubiquitin-binding scaffold protein [22] , [23] .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, different organelle-specific MSR isoforms are present 26 27 . Loss of MSR activity results in augmented brain pathologies associated with neurodegenerative disorders, such as Alzheimer's disease and PD 28 29 30 , and MSRs are thought to exert general protective effects against α-Syn aggregation and cellular oxidative stress-induced apoptosis 31 .…”
mentioning
confidence: 99%